(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
As stated in its statute, the Italian National Institute of Health (Istituto Superiore di Sanità) “pursues the protection of public health, especially through the exercise of research, control, consultancy, regulatory and training activities”. The “Code of Ethics of the Italian National Institute of Health” is divided into five parts: integrity in research, conflicts of interest, trials with human subjects, public health, experiments involving animals. The Code is based on a wealth of established and widely shared values affirmed in the key documents on the subject. The ethical principles, values and criteria affirmed in the Code reflect the multitude and broad range of activities and functions performed by the Institute. An important question is how to define “health”. Beyond the difficulty of defining health is figuring out how to value it and how to weigh the health of a single, identified person against the health of many, unidentified people. The Code helps grapple with these and other difficult questions like the concept of consent. It arises from the ethical principle of patient autonomy. Hence, obtaining consent is a must for anything other than a routine physical examination. It can be defined as an instrument of mutual communication between doctor and patient with an expression of choice by the latter for the doctor to act in a particular way.